Clinical intraocular islet transplantation is not a number issue - Shishido, A. (CellR4 Repair Replace Regen Reprogram, 2016)
It is now well established that beta cell replacement through pancreatic islet transplantation results in significant improvement in the quality-of-life of type 1 diabetes (T1D) patients. This is achieved through improved control and prevention of severe drops in blood sugar levels. Islet transplant therapy is on the verge of becoming standard-of-care in the USA. Yet, as with other established transplantation therapies, there remain hurdles to overcome to bring islet transplantation to full fruition as a long-lasting therapy of T1D. One of these hurdles is establishing reliable new sites, other than the liver, where durable efficacy and survival of transplanted islets can be achieved. In this article, we discuss the anterior chamber of the eye as a new site for clinical islet transplantation in the treatment of T1D. We specifically focus on the common conceptions, and preconceptions, on the requirements of islet mass, and whether or not the anterior chamber can accommodate sufficient islets to achieve meaningful efficacy and significant impact on hyperglycemia in clinical application.